(untitled) (Boletin Médico de Postgrado, 2020)
A correlation-type quantitative investigation was carried out with the aim to evaluate the association between microalbuminuria (MA), high-sensitive C-reactive protein (hs-CRP) and cardiovascular risk (CVR) determined by the Framingham scale in patients with Metabolic Syndrome (MS) who attended the Internal Medicine Service of the Hospital Universitario Dr. Luis Gómez López during the period June 2017-June 2018. Thirty patients were included with an average age of 49.53 ± 13.35 years and female sex predominance. According to the Framingham scale, 73.3% of patients had very high and high CVR. Most patients with very high CVR had elevated levels of hs-CRP. There was a positive and significant correlation between hs-CRP levels and CVR (R=0.533, p <0.05). An early diagnosis of MS is important as a risk factor for the development of cardiovascular disease.